A comunidade de plantas utilizada por beija-flores no sub-bosque de um fragmento de Mata Atlântica da Bahia, Brasil - Coelho, Aline Goes (2013)
Studies on hummingbird/plant interactions in the Atlantic Forest have been providing major data on ornithophilous plants and on the role of these birds as pollen vectors and maintainers of plant communities. The aim of this study was to investigate a plant community used by hummingbirds, in order to recognize flowering phenological patterns and to identify pollen loads transported by visiting trochilidae. Fieldwork was performed from April 2009 to August 2011 in the understory of an Atlantic Forest area within Michelin Ecological Reserve, in Igrapiúna municipality, Bahia State. We identified hummingbirds from focal observations in flowering plants, recording their foraging strategies and the local of pollen deposition in their bodies. Data on morphology and floral biology were recorded for plants visited by hummingbirds, such as the number of flowers and buds monthly produced and if the plant was ornithophilous or not. Pollen attached to the beak, head, throat and chest of captured hummingbirds was removed, identified and counted in laboratory. About 18 plant species, most of them ornithophilous (83%), were visited by 13 hummingbird species, with Phaethornis ruber being the most frequent pollen vector. The plant community showed a continuous flowering, with sequential flowering peaks during the studied period. Sixteen pollen types and eight hummingbird species were recorded, with the beak being the main area for pollen deposition (58%), followed by the head (30%), throat (11%) and chest (1%). Differences on the local of pollen deposition on birds reduce the chance of mixing pollen from different species, allowing their coexistence by the sharing of the same pollen vector. Continuous flowering within the plant community assure the presence of their pollinators in the area, avoiding population dislocation towards floral resources. A high investment on floral morphology specialization allows a great deposition of pollen grains over a safe place on the body of the hummingbirds, maximizing plant reproductive success.